2008
DOI: 10.1097/ana.0b013e3181705cfb
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Paracetamol Improves the Quality of Postoperative Analgesia but Does not Decrease Narcotic Requirements

Abstract: Paracetamol, a centrally acting inhibitor of cyclooxygenase, has less gastrointestinal and platelet-inhibiting side effects and is clinically better tolerated than nonsteroidal anti-inflammatory drugs. Therefore, it will be ideally suited for postoperative pain relief. In this prospective, double-blind, randomized, placebo-controlled study, we evaluated the analgesic efficacy, opioid-sparing effect and effects on opioid-related adverse effects of intravenous (IV) paracetamol in combination with IV morphine aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
64
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 20 publications
(23 reference statements)
10
64
0
2
Order By: Relevance
“…Our results are in concordance with the studies by Yilmaz et al and Cakan et al, although they combined paracetamol with tramadol and morphine 24,29 . Despite the more eff ective control of postoperative pain by opioid analgesics, paracetamol alone may be considered as an effi cacious analgesic for postoperative pain relief following lumbar disc surgery.…”
Section: Fig 1 Diff Erences In Pain Perception Between Study Groupssupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in concordance with the studies by Yilmaz et al and Cakan et al, although they combined paracetamol with tramadol and morphine 24,29 . Despite the more eff ective control of postoperative pain by opioid analgesics, paracetamol alone may be considered as an effi cacious analgesic for postoperative pain relief following lumbar disc surgery.…”
Section: Fig 1 Diff Erences In Pain Perception Between Study Groupssupporting
confidence: 93%
“…Adequate pain management in this period has been observed to correlate well with improved functional outcome, early discharge, better ambulation, and preventing development of chronic pain syndrome 2 . Although opioid analgesics are the most widely used drugs for controlling postoperative pain, some authors have emphasized the use of intravenous paracetamol to improve postoperative pain and increase patient satisfaction following this type of surgery [29][30][31][32] . Th e effi cacy of paracetamol alone in the treatment of mild-to-moderate postoperative pain and its place in combination treatment were investigated [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Çakan ve ark. bizim de çalışmamızda elde ettiğimiz gibi, lomber diskektomi olgularında parasetamolün hasta memnuniyetini artırdığı ancak opioid tüketi-mine etkisi olmadığı tespit etmiştir, [15] ancak çalış-mamızda elde ettiğimiz sonuçtan farklı olarak parasetamolün uygulandığı değişik cerrahi vakalarında opioid azaltıcı etkisi olduğu ve hastanın toplam opioid gereksinimini %24-46 oranında azalttığını ve bunun da analjezik tedavide toplam hasta memnuniyetinin artmasını sağladığı literatürlerde gösterilmiştir. [16] Çalışmamızda VAS değerleri parasetamol grubunda kontrol grubuna göre daha düşük olup toplam tramadol tüketimi arasında fark yoktur.…”
Section: Discussionunclassified
“…However, a recent mixed treatment comparison analysis of 60 relevant clinical studies reported that APAP reduced the amount of morphine required by patients to manage pain in the first 24 hours following major surgery (Maund et al, 2011). This morphinesparing effect was only studied acutely and is not found in all patient populations (i.e., young infants) or following all procedures (i.e., lumbar laminectomy and discectomy, cesarean delivery) (Siddik et al, 2001;van der Marel et al, 2007;Cakan et al, 2008). Taken together, the results of these studies may reflect, in part, altered CNS delivery of morphine as a result of prior or concurrent APAP exposure over time.…”
Section: Discussionmentioning
confidence: 99%